LINGKUNGAN VEGETASI DULU DAN KINI DI SITUS KOBATUWA II, NUSA TENGGARA TIMUR - Vita Matori (Forum Arkeologi, 2013)
Kobatuwa II site is located in the Soa Basin, at an altitude of 345 metres above sea level, surrounded by hills and volcanoes, i.e. to the North is Mount Weawavo, Mount Hill Rega, Nuke, and Mangu, South of there is the mountain Inerie and the mountain Logobada, on the West by Mount Meze (Wolo Meze), on the East by Mount Matataka, in the Southeast by Mount Abulobo astronomically, it lay in the 08 position 41 & 23.5 South latitude and longitude 121 05' & amp; 09,3 " East longitude. The purpose of this research is to know the state of vegetation environment that supports human life and the environment of prehistoric vegetation is now associated with the utilization of the natural resources that exist in the vicinity of the site. The method used is the method the vegetation survey and analysis of sediment pollen (Palinology). The survey results indicate that the site Kobatuwa II this included into the savanna vegetation blend, this is because the savanna in this region is dominated by an open forest canopies are composed by plants in the form of trees and shrubs and layers below it overgrown by a mixture of grasses and shrubs are tolerant of drought. The open Savanna Woodland pastures in this region is the dominant terrestrial type. Tree kesambi (Schleichera oleosa) which is one of the dominant species of tree savanna. From the results of the analysis of pollen while it can be noted that there has been a change in the vegetation which has been proven by the discovery of fossils of the Fagaceae only pollen found in wet forests. There has been also a changes in the vegetation of wet forest to savanna vegetation that is currently dominated by the expanse of grassland.Situs Kobatuwa II terletak di daerah cekungan Soa, pada ketinggian 345 meter dari permukaan laut yang dikelilingi oleh perbukitan dan gunung api, yaitu disebelah Utara Bukit Weawavo, Bukit Rega, Bukit Nuke, dan Bukit Mangu, di Selatan Gunung Inerie dan Gunung Logobada, di Barat Gunung Meze (Wolo Meze), di Timur Gunung Matataka, di sebelah tenggara Gunung Abulobo, secara astronomis terletak pada posisi 0841 23,5 LS dan 12105 09,3 BT. Tujuan penelitian ini untuk mengetahui keadaan lingkungan vegetasi yang mendukung kehidupan manusia prasejarah dan lingkungan vegetasi sekarang yang berkaitan dengan pemanfaatan sumberdaya alam di sekitar situs. Metode yang digunakan adalah metode survei dan analisa polen sedimen (Palinology). Hasil survei menunjukkan bahwa situs Kobatuwa II termasuk ke dalam vegetasi savana campuran, hal ini disebabkan karena savana di wilayah ini didominasi tajuk hutan terbuka yang disusun dari jenis tumbuhan berupa pohon maupun semak belukar dan lapisan bawahnya ditumbuhi campuran rumput dan perdu yang toleran terhadap kekeringan. Savana di daerah ini merupakan jenis terestrial yang dominan. Pohon Kesambi (Schleichera oleosa) merupakan salah satu jenis pohon yang dominan. Dari hasil analisis polen diketahui bahwa telah terjadi perubahan vegetasi sejak dulu, terbukti dengan ditemukannya fosil polen jenis Fagaceae yang hanya terdapat pada hutan-hutan basah. Telah terjadi pula perubahan vegetasi dari hutan basah ke vegetasi savana yang saat ini didominasi oleh hamparan padang rumput.